2018
DOI: 10.2903/j.efsa.2018.5047
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of celluloses E 460(i), E 460(ii), E 461, E 462, E 463, E 464, E 465, E 466, E 468 and E 469 as food additives

Abstract: Following a request from the European Commission, the EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) was asked to deliver a scientific opinion re-evaluating the safety of microcrystalline cellulose (E 460(i)), powdered cellulose (E 460(ii)), methyl cellulose (E 461), ethyl cellulose (E 462), hydroxypropyl cellulose (E 463), hydroxypropyl methyl cellulose (E 464), ethyl methyl cellulose (E 465), sodium carboxy methyl cellulose (E 466), enzymatically hydrolysed carboxy methyl cellulose (E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 154 publications
0
61
0
Order By: Relevance
“…Short-term and subchronic dietary toxicity evaluation did not reveal adverse effects. Chronic toxicity studies showed NOAEL values up to 9000 mg/kg/day, no carcinogenic properties or adverse effects on reproductive performance were observed [189].…”
Section: Safety and Potential Toxicity Of Cellulose Micro And Nanostructuresmentioning
confidence: 93%
“…Short-term and subchronic dietary toxicity evaluation did not reveal adverse effects. Chronic toxicity studies showed NOAEL values up to 9000 mg/kg/day, no carcinogenic properties or adverse effects on reproductive performance were observed [189].…”
Section: Safety and Potential Toxicity Of Cellulose Micro And Nanostructuresmentioning
confidence: 93%
“…The latest evaluation of enzymatically hydrolyzed CMC was conducted in 1998, and an ADI ‘not specified’ was established [ 23 ]. Following a request from the European Commission, the EFSA Panel on Food Additives and Nutrient Sources added to food delivered a scientific opinion re-evaluating the safety of CMC as a food additive [ 24 ]. The Panel concluded that there was no need for a numerical ADI and suggested an indicative daily consumption value of 660−900 mg/kg body weight per day.…”
Section: Emulsifiers In Processed Foodsmentioning
confidence: 99%
“…As food additives, micron and colloidal plant cellulose and their derivatives are approved for human consumption by several regulatory authorities, such as the FDA (Food and Drug Administration, Silver Spring, MD, USA) and the EC (European Commission); they are regularly applied in the food industry to regulate its texture, stability, rheology and organoleptic features [ 8 , 9 ]. In the 1980s, plant nanocellulose was first suggested as a human food additive with enormous potential, as its high aspect ratio could confer new physicochemical properties and behaviors to foods [ 10 ].…”
Section: Introductionmentioning
confidence: 99%